A Critical Review of Non-Pharmacological Interventions for Dysmenorrhea Management in Adolescents - Arifah Septiane Mukti; Kurniati Devi Purnamasari; Yudita Ingga Hindiarti (Journal of Midwifery and Public Health, 2025)
Background: Dysmenorrhea is a common reproductive health problem among adolescents that negatively affects academic activities, social participation, and quality of life. Non-pharmacological interventions are increasingly used as alternative or complementary approaches for menstrual pain management. Objective: To critically review the effectiveness of non-pharmacological interventions in managing dysmenorrhea among adolescents. Methods: This study employed a critical literature review with a systematic search approach guided by PRISMA principles across PubMed, Scopus, ScienceDirect, and Google Scholar databases from 2021–2025. Articles were selected using predefined inclusion and exclusion criteria and analyzed through narrative synthesis. Results: A total of 15 studies were included. Heat therapy, exercise, and yoga demonstrated the most consistent evidence in reducing dysmenorrhea pain, while relaxation, aromatherapy, music therapy, and herbal interventions provided additional benefits. Conclusion: Non-pharmacological interventions are effective in managing adolescent dysmenorrhea; however, standardized protocols and higher-quality studies remain necessary.